2019
DOI: 10.1080/14786419.2019.1587427
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the phytochemical composition, enzyme inhibition and antioxidant properties of desert cotton (Aerva javanica (Bum.f) Shult. -Amaranthaceae)

Abstract: This study sets out to probe into total bioactive contents, UHPLC-MS secondary metabolites profiling, antioxidant (DPPH, ABTS, FRAP, CUPRAC, phosphomolybdenum and metal chelating) and enzyme inhibitory (acetylcholinesterase-AChE, butyrylcholinesterase-BChE, α-amylase, α glucosidase, and tyrosinase) activities of methanol extract of Aerva javanica, also known as desert cotton or Kapok bush. Aerva javanica contains considerable phenolic (44.79±3.12 mg GAE/g) and flavonoid (28.86±0.12 mg QE/g) contents which tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Similar to our results various chemical and nutritive compounds like lipids, flavonoids, steroids, triterpenes, alkaloids, tannins, saponins, carbohydrates, sulphates and glycosides were also reported by other researchers (Reddy and Reddy 2009;Munir et al 2014). Inhibitory studies encourage its phytochemicals be potential remedy for diseases like skin hyperpigmentation, Alzheimer and stress complications (Saleem et al 2021). It was concluded from analysis that the plant parts contained significant amounts of total phenolics and flavonoids, which may be the cause of their successful medicinal use.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results various chemical and nutritive compounds like lipids, flavonoids, steroids, triterpenes, alkaloids, tannins, saponins, carbohydrates, sulphates and glycosides were also reported by other researchers (Reddy and Reddy 2009;Munir et al 2014). Inhibitory studies encourage its phytochemicals be potential remedy for diseases like skin hyperpigmentation, Alzheimer and stress complications (Saleem et al 2021). It was concluded from analysis that the plant parts contained significant amounts of total phenolics and flavonoids, which may be the cause of their successful medicinal use.…”
Section: Discussionmentioning
confidence: 99%
“…Aj.Cr therapy increased BDNF owing to quercetin and kaempferol, which have an anti-depressant impact through the BDNF-TrkB-PI3K/Akt regulation pathway. 98 , 99 A prior research on bioactive components of Aj.Cr found kaempferol and its glycoside derivatives, such as kaempferol3-(2G-glucosylrutinoside), kaempferol 3-(2,3-diacetyl –4“-(Z)-p-coumaryl-6”-(E)-p-coumarylglucoside), kaempferol 3-neohesperidoside 100 Kaempferol and kaempferol-3-O-glucoside exhibit anti-depressant effects due to their antioxidant activity, pro-inflammatory cytokine reduction, AKT/-catenin cascade enhancement, and imipramine tolerance reversed. 101 , 102 Chronic exposure to high amounts of inflammatory cytokines and continuous variations in central neurotransmitters may enhance oxidative stress and injure microglial cells 103 by activating NF-kB and boosting the production of the i-NOS gene.…”
Section: Discussionmentioning
confidence: 99%
“…27 They found that the TPC and TFC values of these fruits ranged from 360.81 to 398.48 mg GAE/g and 13.69 to 23.87 mg QE/g, respectively. Other recent studies have reported TPC and TFC values for a variety of plant extracts, including Salvia aytachii ethyl acetate extract (TFC 22.33 ± 0.17 μg QE/mg), 46 seeds of seven sunflower methanol extracts (TPC 22.29-33.09 mg GAE/g), 47 sea cucumber tentacles (TPC 2.4138 mg GAE/g), 48 Ficus sycomorus L. hexane extract (TPC 1980.4 mg GAE/g; TFC 109.9 mg QE/g), 1 Aerva javanica methanol extract (TPC 44.79 mg GAE/g; TFC 28.86 mg QE/g), 49 and Australian native fruits (TPC 23.04 to 74.84 mg GAE/g and TFC 8.31 to 20.63 mg QE/g). 50 These findings demonstrate the wide range of TPC and TFC values that can be obtained from different plant extracts and highlight the importance of carefully selecting the extraction method and solvent to obtain accurate and reliable results.…”
Section: Phytochemical Screeningmentioning
confidence: 99%